The effect of internal control on earnings quality in Iran - (:unkn) unknown (EMERALD GROUP PUBLISHING LTD, 2017)
Purpose - The purpose of the present research is to examine the effect of internal control and risk management on earnings quality of companies listed on the Tehran Stock Exchange (TSE). Design/methodology/approach - Data were collected from 560 listed firms on TSE, which were selected using systematic sampling. Descriptive statistics, Pearson correlation and panel data regression were used for data analysis during 2009-2014. Findings - The results showed that earnings management reduces earnings relevance and book value relevance through short-term and long-term discretionary accruals. Originality/value - The outcomes of the current study are quite interesting to academia and practitioners.
Keywords: Internal control; Earnings quality; Risk management; Discretionary accruals; PERFORMANCE; DIVIDENDS; ACCRUALS